2017
DOI: 10.1525/elementa.254
|View full text |Cite
|
Sign up to set email alerts
|

Surface ozone in the Colorado northern Front Range and the influence of oil and gas development during FRAPPE/DISCOVER-AQ in summer 2014

Abstract: High mixing ratios of ozone (O3) in the northern Front Range (NFR) of Colorado are not limited to the urban Denver area but were also observed in rural areas where oil and gas activity is the primary source of O3 precursors. On individual days, oil and gas O3 precursors can contribute in excess of 30 ppb to O3 growth and can lead to exceedances of the EPA O3 National Ambient Air Quality Standard. Data used in this study were gathered from continuous surface O3 monitors for June–August 2013–2015 as well as addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 35 publications
4
46
0
Order By: Relevance
“…Thus, the idealized BOXMOX simulations support our empirical conclusion that VOCs from oil and natural gas activities contribute to O 3 production on high O 3 days. This is consistent with the findings from several other recent studies on O 3 in the northern Colorado Front Range using a variety of different methods (e.g., Cheadle et al, 2017;Evans & Helmig, 2017;McDuffie et al, 2016;. 4.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Thus, the idealized BOXMOX simulations support our empirical conclusion that VOCs from oil and natural gas activities contribute to O 3 production on high O 3 days. This is consistent with the findings from several other recent studies on O 3 in the northern Colorado Front Range using a variety of different methods (e.g., Cheadle et al, 2017;Evans & Helmig, 2017;McDuffie et al, 2016;. 4.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the idealized BOXMOX simulations support our empirical conclusion that VOCs from oil and natural gas activities contribute to O 3 production on high O 3 days. This is consistent with the findings from several other recent studies on O 3 in the northern Colorado Front Range using a variety of different methods (e.g., Cheadle et al, ; Evans & Helmig, ; McDuffie et al, ; Pfister, Flocke, et al, ). Out of the VOC species that were measured, propane and several larger alkanes such as n‐pentane are the dominant contributors to PPN production in the BOXMOX simulations. In the northern Colorado Front Range, these species predominately come from oil and natural gas sources (e.g., Abeleira et al, ; Gilman et al, ) and thus indicate that high ratios of PPN/PAN observed in the northern Colorado Front Range are driven by the oxidation of emissions from oil and natural gas production.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other recent research building on campaign observations has provided observational and modeling evidence that O&NG emissions significantly contribute to summer O 3 production within the DJB and NCFR downwind regions (Gilman et al, 2013;Swarthout et al, 2013;McDuffie et al, 2016;Pfister et al, 2017;Cheadle et al, 2017). This association is difficult to prove with the data and tools that were applied here.…”
Section: Ozone and Oandng Developmentmentioning
confidence: 85%